Bimorphic microstructure in Ti-6Al-4V alloy manipulated by spark plasma sintering and in-situ press forging. (1st March 2021) - Kang, L.M.; Cai, Y.J.; Luo, X.C.; Li, Z.J.; Liu, X.B.; Wang, Z.; Li, Y.Y.; Yang, C.
Abstract: We report on a methodology of powder sintering and in-situ press forging, which can be used to manipulate a new bimorphic microstructure in Ti-6Al-4V alloy. The microstructure contains typical triangle colonies with ultrafine lamellar α and β, and their border areas with ultrafine equiaxed α, dispersed nano/ultrafine β, as well as α/β interface L layers. Surprisingly, the bimorphic alloy exhibits excellent mechanical properties under both tensile and compressive conditions, far superior to other Ti-6Al-4V alloys and their composites reported so far. Therefore, this innovative methodology provides a simple and economical method for preparing high-performance metallic alloys in structural applications. Graphical abstract: We report on an innovative methodology of spark plasma sintering and in-situ press forging, which can be used to manipulate a new bimorphic microstructure in Ti-6Al-4V alloy. Surprisingly, the manipulated bimorphic alloy exhibits excellent mechanical properties under both tensile and compressive conditions, far superior to other Ti-6Al-4V alloys and their composites reported so far. Image, graphical abstract